The methodology of al-Tafsir al-Mawdu'i:a comparative analysis - El-Mesawi, Mohamed El-Tahir (IIUM Press, 2005)
The notion of thematic interpretation of the Qur'an (al-tafsir al-mawdu'i) has attained a remarkable degree of conceptual and methodological clarity in the works of Muhammad Abdallah Draz, Muhammad Mahmud Hijazi, Muhammad Baqir al-Sadr and Fazlur Rahman. They provide cases that allow testing of methodological feasibility and intellectual fecundity of this approach to Qur'anic exegesis. A common and important aspect of their works, as the textual analysis shows, is the attempt to search for a Qur'anic conceptual framework for social theorization informed and guided by the fundamental Islamic world-view.